Marco Calliari, an Italian-Quebecois Artist. A Reflection of Identity, Cultural Belonging and Artistic Patrimony - Aloisio, Anita (Oltreoceano - Rivista sulle migrazioni, 2021)
The following article explores the distinctive creative process that Italian-Quebecois artists undergo and how it is reflected in their work. The Italian-Quebecois artist strives to achieve a balance between family tradition, their parents’ experience of immigration, identity and personal creativity. Their journey is a testament to a rising artistic patrimony that has yet to be categorized by academia. Marco Calliari, artista italo-quebecchese. Una riflessione sull’identità, sull’appartenenza culturale e sul patrimonio artistico Il presente articolo esplora il percorso creativo degli artisti italo-quebecchesi. Lo studio analizza la ricerca constante di un equilibrio fra tradizioni culturali e familiari tramandate dai propri genitori immigranti con l’identità e creatività personale manifestate dalle loro opere. Un testamento originale di un patrimonio artistico quebecchese non ancora pienamente valorizzato dal mondo accademico.